TANTANGAN DAN PELUANG REAKTUALISASI TEORI SOSIAL PROFETIK KUNTOWIJOYO DALAM MENANAMKAN SOFT SKILLS KEWIRUSAHAAN DI INDONESIA - Devi, Yuliani Sari (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
The cultivation of soft skills in entrepreneurship in Indonesia is a key element in facing the challenges of globalization, technology, and increasingly competitive economic competition. Kuntowijoyo's Social Prophetic Theory presents an alternative perspective that combines religious values and ethics in the process of entrepreneurial development, especially in shaping soft skills based on moral and religious ethics. This article explores the challenges and opportunities in integrating humanism, liberation, and transcendence into the formation of entrepreneurial soft skills in Indonesia. This article uses a qualitative descriptive approach, literature study, and secondary data methods. There are several mapped challenges and opportunities in actualizing Kuntowijoyo's Social Prophetic Theory to foster entrepreneurial soft skills based on religious ethics and morals.